Status of indigenous ornamental plants in India - Janakiram, T; Safeena, S A; Prasad, K V (Indian Horticulture, 2019)
The total geographical area of India is estimated to be about 329 million hawith a coastline ranging over 7,500 km. The ecosystem or ecological diversityprevailing in our country is enormous, ranging from sea level to the highestmountainous ranges; hot and arid conditions in the northwest to cold aridconditions in the trans-Himalayan region; tropical wet evergreen forests inNortheast India and the Western Ghats; mangroves of Sundarbans andfreshwater aquatic to marine ecosystems. India is reported to have 12 biogeographicalprovinces, 5 biomes and 3 bioregion domains. India is rich invaried array of ecosystem or habitats like forests, grasslands, wetlands, coastal,marine and desert along with rich and unique diversity of flora and fauna.